NALAR KRITIS BERBASIS ISU KONTEMPORER DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Lalu Muhammad Samiuddin; Ali Imran (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
The aim of this research is to find out and describe as well as an effort to improve students' critical reasoning through contemporary issues. Contemporary issues are problems that have been discussed previously but still attract interest to be studied again and have relevance to Islamic Religious Education (PAI). One of the PAI groups is Fiqh subjects which are indirectly closely related to the study of interpretation, so they must involve critical reasoning in order to obtain a comprehensive understanding. Contemporary issues include gender and leadership issues. In the research used is a qualitative research method with a descriptive approach. In this research, the author tried to collect various book and journal sources related to critical reasoning. This research uses library research or what is often called library research. The results of the research show several things, including first, the variety of meanings presented by the interpreters is basically aimed at helping to simplify and understand the content of the Al-Qur'an. Second, the new issues that emerge are basically opportunities for thinkers (interpreters) to find goodness in their lives. Third, the emergence of new issues cannot be separated from the will of Allah SWT to give birth to new generations who are capable of relying on his thoughts. In other words, contemporary issues serve as a forum for training and strengthening critical reasoning, and of course become part of the treasures of Islamic Religious Education.